Estimating $$χ _top$$ χtop lattice artifacts from flowed SU(2) calorons - P. Thomas Jahn (European Physical Journal C: Particles and Fields, 2019)
Abstract Lattice computations of the high-temperature topological susceptibility of QCD receive lattice-spacing corrections and suffer from systematics arising from the type and depth of gradient flow. We study the lattice spacing corrections to $$χ _top$$ χtop semi-analytically by exploring the behavior of discretized Harrington–Shepard calorons under the action of different forms of gradient flow. From our study we conclude that $$N_τ = 6$$ Nτ=6 is definitely too small of a time extent to study the theory at temperatures of order $$4~T_c$$ 4Tc and we explore how the amount of gradient flow influences the continuum extrapolation.